Geochemical investigation, oil–oil and oil–source rock correlation in the Dezful Embayment, Marun Oilfield, Zagros, Iran. (December 2015) - Asadi Mehmandosti, Elham; Adabi, Mohammad Hossein; Bowden, Stephen A.; Alizadeh, Bahram
Abstract: Geochemical analysis of crude oils from Bangestan and Khami reservoirs, and potential source and reservoirs rocks from the Marun Field in the Dezful Embayment, Zagros Fold Belt Iran show that the Kazhdumi Formation (Fm.) is likely to be thermally mature (at least in the oil window) across the entirety of the Marun field, and that it has excellent generative potential as a source rock. Geochemical data also suggest the Pabdeh Formation has remarkable generative potential but is not thermally mature at the crest of the Marun field, although it is likely to be thermally mature in synclinal regions to the NE and SW. The Gurpi Formation, while thermally mature (early oil window) has marginal generative potential. It is notable, therefore, that oils from the Bangestan and Khami reservoirs have biomarker characteristics that do not match bitumen obtained from the Kazhdumi Formation. Examples of this include the ratio of diasteranes to steranes, the proportions of different carbon numbered hopane homologues and the ubiquitous occurrence of alkylated-trimethyl-benzenes. These biomarker characteristics could only have been imparted to the Bangestan and Khami oils by a source rock other than the Kazhdumi Formation. This contrasts with the stable isotope composition of the Bangestan and Khami oils which suggest correlation to the Kazhdumi Formation. Biomarkers are a quantitatively minor fraction of oil, thus it is possible that the biomarker characteristics of the oils was created by mixing Kazhdumi-bitumen with other petroleum from the Gurpi and Pabdeh formations. This could happen if 1) multiple oil charges from different source kitchens filled the same reservoir, or 2) if oil migrated vertically from the flanks and crossed the Gurpi and Pabdeh formations – both of which have been considered regional seals. Both scenario 1) or 2) would point to a filling history more complicated than previously conceived. Highlights: Assessment of source potential of source rocks in Zagros, Iran. New biomarker data for correlating source rocks and oils in region. Biomarker data for Bangestan, as well as other smaller reservoirs yet to be exploited. Confirmation of Pabdeh source rock signal in some oil. There are not many papers on the region in the last few years.